Over a million students use our free study notes to help them with their homework
A) 4(cosec2(2x)) - (cosec2(x)) = 4/(sin2(2x)) - 1/(sin2(x)) = 4/[(2 sin(x) cos(x))2] - 1/(sin2(x)) B) 4/[(2 sin(x) cos(x))2] - ...
As we are given the derivative of f(x), we first need to integrate this derivative to obtain the function, f(x). Using the standard integration formula, ∫ x^n dx = (1/n+1)(x^(n+1)) +c, integrate each term...
Here, we use integration by parts. We must imagine ln(x) as a product of 1 and ln(x). We usually take the function of x to be our dv/dx, however, in the case of ln(x), we take that to be u (it is a specia...
This problem uses the binomial expansion formula: (x+y)n= k=0Zn nCk xk yn-k.But lets try to understand where this formula comes...
←
253
254
255
256
257
→
Internet Safety
Payment Security
Cyber
Essentials